Purification of conjugated polymers. Better polymers through HPLC purification and Soxhlet extraction - Öhberg, Jessika (My University, 2024)
Abstract The purification of conjugated polymers, specifically the polymer D18, was investigated using the purification methods of Soxhlet extraction and High-Performance Liquid Chromatography (HPLC). The objective was to purify D18 from residual Pd impurities remaining from synthesis and fractionate the molecular weight for lower dispersity and higher molecular weights. This is crucial for conjugated polymers like D18, as with robust and effective purification methods, they have a prominent future as materials extensively used in organic electronic devices such as solar cells. The purification process has a significant impact on the polymer’s properties, influencing its electronic and optical performance which highlights the importance of standardized purification and reproducible results. The study demonstrates that while Soxhlet extraction was effective in removing low molecular weight fractions, HPLC proves to be superior in narrowing down the dispersity and reducing palladium (Pd) content for the polymer D18. The work also investigates the use of TOF-SIMS for measuring Pd content before and after purification by developing a calibration curve. Two palladium complexes, Pd(PPh3)4 and Pd2(dba)3 chloroform adduct, were along with the polymer P3HT used to create calibration curves, with Pd2(dba)3 showing better performance due to its solubility and stability. Challenges included potential contamination, suggesting the need for stricter environment protocols for sample handling. Calculating the Pd content from the calibration curves underscored the importance of a robust normalization technique to obtain absolute quantification. This research provides insights into purification methods that can enhance the performance of conjugated polymers in organic electronic applications and demonstrates the use of TOF-SIMS as an evaluation method of metal impurities. Keywords: Conjugated polymers, Purification, Soxhlet extraction, HPLC, TOFSIMS.
Keywords: Conjugated polymers; Purification; Soxhlet extraction; HPLC; TOFSIMS